1995
DOI: 10.1139/b95-291
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification of phytoanticipins and phytoalexins by phytopathogenic fungi

Abstract: Most plants synthesize antimicrobial compounds as part of normal plant development (i.e., phytoanticipins) or synthesize such compounds de novo when challenged by microorganisms (i.e., phytoalexins). The presumed role of these plant antibiotics is to protect the plant from disease. However, many phytopathogenic fungi have enzymes that can detoxify the phytoanticipins or phytoalexins produced by their host. This may be a means that these pathogens have evolved to circumvent resistance mechanisms based on the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(39 citation statements)
references
References 38 publications
0
39
0
Order By: Relevance
“…43% of the initial amount of 1 detected after incubation for 110 h. On the other hand, a contrasting trend was observed for the metabolism of hydroxydestruxin B (3) to ␤-D-glucosyl hydroxydestruxin B (5); cultivars of B. napus (S) appeared to transform hydroxydestruxin B (3) to 5 substantially faster than cultivars of S. alba (R), whereas Cutlass (B. juncea, S) showed an intermediate rate. Most importantly, leaf and cell culture assays showed that hydroxydestruxin B (3) was substantially less toxic to any of the species tested than destruxin B (1), and ␤-D-glucosyl hydroxydestruxin B (5) showed no toxicity at all ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…43% of the initial amount of 1 detected after incubation for 110 h. On the other hand, a contrasting trend was observed for the metabolism of hydroxydestruxin B (3) to ␤-D-glucosyl hydroxydestruxin B (5); cultivars of B. napus (S) appeared to transform hydroxydestruxin B (3) to 5 substantially faster than cultivars of S. alba (R), whereas Cutlass (B. juncea, S) showed an intermediate rate. Most importantly, leaf and cell culture assays showed that hydroxydestruxin B (3) was substantially less toxic to any of the species tested than destruxin B (1), and ␤-D-glucosyl hydroxydestruxin B (5) showed no toxicity at all ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, such detoxification traits are desirable and of much importance in strategic plant breeding or in engineering disease resistance. Whereas a number of phytoalexin detoxifying reactions have been shown to occur in very diverse plant pathogenic fungi (1,5,6), detoxification of phytotoxins has been reported in only a few plant species (7).…”
mentioning
confidence: 99%
“…Fungal detoxification of plant antimicrobial compounds is known to enhance virulence and in some associations is essential for pathogenicity (8,11,43,50,52). Determining if a correlation exists between benzoxazinoid detoxification and fungal virulence depends on measurement of in planta aspects of infection, colonization, and compatibility.…”
Section: Discussionmentioning
confidence: 99%
“…However, whereas preformed inhibitors may be effective against a broad spectrum of potential pathogens, successful pathogens are likely to be able to circumvent the effects of these antibiotics either by avoiding them altogether or by tolerating or detoxifying them (Schonbeck and Schlosser, 1976;Fry and Myers, 1981;Bennett and Wallsgrove, 1994;VanEtten et al, 1995;Osbourn, 1996). The isolation of plant mutants defective in the biosynthesis of preformed inhibitors would allow a direct genetic test of the importance of these compounds in plant defense.…”
Section: Introductionmentioning
confidence: 99%